Transformasi Inovasi Pelayanan Publik Berkelanjutan di Kabupaten Banyuwangi: Strategi Akselerasi Pembangunan menuju Visi Indonesia Emas 2045: (Transforming Sustainable Public Service Innovation in Banyuwangi Regency: Strategies to Accelerate Development Toward the “Golden Indonesia 2045” Vision) - Zulmasyhur (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
The Indonesia Gold 2045 Vision mandates a government governance transformation that is not only adaptive but also sustainable. Banyuwangi Regency has become a recognized locus of public service innovation, yet a deep synthesis of its acceleration strategy is required for macro-policy replication. Objective: This study aims to analyze the typology of innovation, its contribution to the Sustainable Development Goals (SDGs), and the driving and inhibiting factors in the sustainability of public service innovation in Banyuwangi. Methods: This study employs a qualitative approach using the Systematic Literature Review (SLR) method following the PRISMA protocol. The analysis was conducted on 25 high-quality journal articles published between 2014 and 2024. Results: The findings indicate a convergence between digital, organizational, and process innovations that create an inclusive service ecosystem. Innovations such as